2018
DOI: 10.1155/2018/1067672
|View full text |Cite
|
Sign up to set email alerts
|

Solar Drying and Sensory Attributes of Eland (Taurotragus oryx) Jerky

Abstract: A double-pass solar drier (DPSD) and a laboratory oven (LO) were used for thin-layer drying of eland and beef. Prior to drying, the physicochemical characteristics of the raw meat were determined, such as pH, dry matter content (%), Warner-Bratzler shear force (N), pigment concentration (mg·kg−1), weight loss during cooking (%), water holding capacity (%), colour (L,a,b), and crude fat content (%). Both meats were pretreated with traditional jerky marinade (TM), TM with fresh pineapple juice (TMP), TM with hon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…e effect of light exposure on the color of the watermelon is listed in Table 1. Usually, the color can be discriminated when the color difference (ΔE) was higher than 3.0 [28]. e ΔE of the blue exposure and the control was 3.36 and 5.00, respectively, while that of the red and green exposures was 0.58 and 2.47, respectively.…”
Section: Effect Of Light Exposures On Appearance Of Fresh-cutmentioning
confidence: 99%
“…e effect of light exposure on the color of the watermelon is listed in Table 1. Usually, the color can be discriminated when the color difference (ΔE) was higher than 3.0 [28]. e ΔE of the blue exposure and the control was 3.36 and 5.00, respectively, while that of the red and green exposures was 0.58 and 2.47, respectively.…”
Section: Effect Of Light Exposures On Appearance Of Fresh-cutmentioning
confidence: 99%
“…The variation in the composition of each muscle depends on various factors mentioned above. The moisture content in the sample is very important for the drying process, since it largely depends on the time required to achieve the desired final product moisture Kucerova et al 12 It can be seen that the cut glove had the highest content 76.42%. Figure 1 shows the drying curves for each meat cut and can be observed that the three presented a similar behavior.…”
Section: Physicochemical Characteristics Of the Raw Materialsmentioning
confidence: 99%